(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to investigate the effectiveness of a training program based on the (TPACK) model in improving productive disposition among primary school mathematics teachers, the guide for the training program and study tools was prepared, ensured their validity and stability. The guideline included the definition of the (TPACK) model with algebraic context. An available sample was selected from the schools of Jerash Kasbah of the Directorate of Education of Jerash Governorate, consisting of (36) primary mathematics teachers, divided into two groups: one experimental consisted of (18) teachers trained according to the (TPACK) model, the other was a control group consisted of (18) teachers who did not undergo training. The results showed that training according to (TPACK) model improved the level of performance of the experimental group mathematics teachers on the productive disposition scale, and raised Their performance to an expert level, in the light of the results presented the change of the recommendations of the training programs with the application of specific educational content and integration models.